Ethische Bildung in Gesundheitssorge, Seelsorge, Lehre und Sozialer Arbeit - Wittrahm, Andreas (European Journal of Mental Health, 2015)
Ethics Training in the Fields of Healthcare, Pastoral Care, Education and Social Work: In an ideologically diverse society, moral consensus is not self-evident. The values, norms, convictions, and attitudes of those working in healthcare, the social sphere, education, and pastoral care are different. It is also becoming less and less common for the organisations of these work areas and their own colleagues to have identical views. Last but not least, the often contradictory expectations of the clients or patients should also be taken into account. In these situations, the representatives of the relationship sessions, supported by those maintaining their institutions, need to learn to reflect on their own moral conceptions, to justify them, and to reach an agreement with each other. This is what we call ‘ethics training’. This ethics training has a developmental psychological aspect too, which we outline based on works by L. Kohlberg and F. Oser. In the case of relationship sessions, however, ethics training needs permanent practising and can be practised in the course of work. The model of consensual ethical decision-making was worked out by W. Heffels. This model facilitates good decisions in disputable practical situations, supports participants in developing their ethical competence, and is applicable in basic and more advanced trainings alike. The introductory phase of the ethics training taking place in a postmodern era is concluded by a review of the toolbar of on-the-spot ethical consultation.